Tax Revenue Strategy In Indonesia 2015 To 2024: : Hpp Law, Digitalization, And Commodity Cycle - Sri Maryanti; Prama Widayat (ADPEBI International Journal of Business and Social Science, 2026)
Taxes provide the majority of Indonesia's State Revenue and Expenditure Budget (APBN). The purpose of this study is to examine trends and the composition of tax revenue, assess the impact of the Harmonization of Tax Regulations Law (UU HPP) and the digitalization of the Directorate General of Taxes (DJP), and evaluate how commodity prices and global economic cycle dynamics influence tax revenue performance from 2015 to 2020. The methods used include descriptive analysis of tax revenue trends and the tax-to-GDP ratio, as well as log-log regression with annual data from the Directorate General of Taxes (DJP), the State Budget (APBN KiTa), the OECD, the Central Bureau of Statistics (BPS), and the IMF. The results show that tax revenue increased from Rp1,240.4 trillion in 2015 to Rp1,867.9 trillion in 2023, although it decreased again in 2024. According to elasticity estimates, the tax buoyancy against GDP is 0.71 (inelastic) and commodity prices are 0.86 (significant). After the HPP law reform, the tax ratio increased to 12.0% in 2023. While digitalization hasn't had a significant impact yet, the dummy HPP Law has a small but positive impact. The research findings indicate that economic recovery and the commodity boom were more dominant than short-term structural reforms in improving the tax ratio after 2021. Policy recommendations include diversifying the tax base, accelerating administrative digitalization, expediting the implementation of the HPP Law, and enhancing fiscal stabilization instruments.